Chronic Red Bull Consumption during Adolescence: Effect on Mesocortical and Mesolimbic Dopamine Transmission and Cardiovascular System in Adult Rats - Vargiu, Romina (Pharmaceuticals (Basel), 2021)
Energy drinks are very popular nonalcoholic beverages among adolescents and young adults for their stimulant effects. Our study aimed to investigate the effect of repeated intraoral Red Bull (RB) infusion on dopamine transmission in the nucleus accumbens shell and core and in the medial prefrontal cortex and on cardiac contractility in adult rats exposed to chronic RB consumption. Rats were subjected to 4 weeks of RB voluntary consumption from adolescence to adulthood. Monitoring of in vivo dopamine was carried out by brain microdialysis. In vitro cardiac contractility was studied on biomechanical properties of isolated left-ventricular papillary muscle. The main finding of the study was that, in treated animals, RB increased shell dopamine via a nonadaptive mechanism, a pattern similar to that of drugs of abuse. No changes in isometric and isotonic mechanical parameters were associated with chronic RB consumption. However, a prolonged time to peak tension and half-time of relaxation and a slower peak rate of tension fall were observed in RB-treated rats. It is likely that RB treatment affects left-ventricular papillary muscle contraction. The neurochemical results here obtained can explain the addictive properties of RB, while the cardiovascular investigation findings suggest a hidden papillary contractility impairment.